Surgical Attire – A Matter of Preference or Evidence? - Spruce, Lisa (Operating Room Nurses Association of Canada Journal, 2016)
Surgical attire can be an emotional and controversial topic among health care providers. The reality, however, is that exposing perioperative patients to the skin and hair of the perioperative team members may be putting patients at risk for a surgical site infection.